Functionalised multi-walled carbon nanotubes-based electrochemical sensor: synergistic effect of graphitisation and carboxylation on detection performance of methyl parathion. (29th July 2022) - Guo, Meimei; Zhu, Gan; Liu, Yunhang; Zhao, Mengyuan; Shen, Yansheng; Zhou, Yu; Liu, Runqiang; Zhao, Hongyuan
ABSTRACT: Efficient and sensitive detection of methyl parathion (MP), an insecticide, is of great significance to food safety and healthy life. In this work, functionalised multi-walled carbon nanotubes after graphitisation and carboxylation (FCNTGC) were applied as a sensitising agent to fabricate the glassy carbon electrode (GCE). The obtained FCNTGC/GCE sensor was successfully used for the sensitive detection of MP. The graphitisation of carbon nanotubes contributes to enhancing the conductive property, and the carboxylation of carbon nanotubes contributes to improving the dispersibility of carbon material. The combination of graphitisation and carboxylation could effectively enhance the electrochemical sensing property towards MP. The fabricated FCNTGC/GCE sensor showed a low limit of detection of 0.00306 μM in a linear concentration range of 0.01–10 µM. In addition, good repeatability and reproducibility could be obtained for the MP detection with the fabricated sensor.